Formulation and Evaluation of the Antidiabetic, Hypolipidemic and Antioxidant Potential of the Tablets of Arbortristoside-A from the Seeds of Nyctanthes arbortristis Linn. - Das, Sanjita; Khan, Irfan; Dhasmana, Shruti; Shrivastava, Shivani; Singh, KM Renu (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: Literature shows the traditional as well as scientific proven medicinal importance of Nyctanthes arbortristis Linn. In the it was aimed at to formulate and screen the antidiabetic, hypolipidemic and antioxidant properties of the tablets of arbortristoside-A obtained from N. arbortristis seeds. Materials and Methods: Arbortristoside-A was chemically isolated from the seeds’ ethanolic extract of N. arbortristis. The antioxidant property of arbortristoside-A was screened in-vitro by the help of DPPH (2,2-diphenyl-1-picrylhydrazyl) methodology. The granules of arbortristocide-A with suitable excipients were prepared by wet granulation method. The tablets were prepared by the help of rotating punch tablet machine and subjected to standard evaluation process. Its antidiabetic property was evaluated by using streptozotocin-induced diabetic wistar rats of either sex. This study also included a serum biochemical assays and pancreatic and hepatic histopathological modification. Results: Daily oral treatment with tablets of arbortristoside-A and glibenclamide (10 mg/kg) for three weeks reduced the plasma glucose, cholesterol, triglycerides, AST and ALT levels significantly whereas improvement in HDL-cholesterol level was observed (p<0.01) as that of the diabetic control animals. Significant recovery of the pancreas and liver was observed with the tablets administration which was supported by its significant antioxidant activity. Conclusion: Present results indicated that the tablets of arbortristoside-A have prominent effect in the overall management of diabetes mainly at its higher dose (75 mg/kg) in the diabetic due to its antilipidemic and antioxidant properties.
Keywords: Antioxidant; antidiabetic; tablet; arbostristoside-A; DPPH; streptozotocin; histopathology